Static Analysis for Java Servlets and JSP - Kirkegaard, Christian; Møller, Anders (BRICS Report Series, 2006)
We present an approach for statically reasoning about the behavior of Web applications that are developed using Java Servlets and JSP. Specifically, we attack the problems of guaranteeing that all output is well-formed and valid XML and ensuring consistency of XHTML form fields and session state. Our approach builds on a collection of program analysis techniques developed earlier in the JWIG and XACT projects, combined with work on balanced context-free grammars. Together, this provides the necessary foundation concerning reasoning about output streams and application control flow.